The Determinants of Stock Price Volatility in Indonesia - Sutrisno, Bambang (EAJ (Economic and Accounting Journal), 2020)
Volatility is a statistical measure of stock price fluctuation. This study aims to investigate the effect of trading volume, firm size, inflation, and exchange rate on stock price volatility of the companies included in the Jakarta Islamic Index (JII) from 2014 to 2018. By using a purposive sampling technique, the research sample is sixteen companies. This research employs panel regression with annual data. This study reveals that trading volume has a significant positive effect on stock price volatility. Firm size has a significant negative impact on stock price volatility. Meanwhile, the inflation and exchange rate do not affect stock price volatility.